PEMBERDAYAAN PEMBERDAYAAN MASYARAKAT DAN KELOMPOK TANI DALAM PEMANFAATAN LIMBAH PERTANIAN MENJADI PUPUK ORGANIK - Novisrayani Kesmayanti; Bahrul Ilmi; Abdul Azis (Jurnal Masda, 2022)
The Setunggal Jaya women’s farmer group and the community in 8 Ilir Village, Palembang City, cultivate vegetable crops as a source of income and fulfillment of food, as well as family nutrition. However, they have not utilized the waste left over from their harvest, while its potential as organic fertilizer is very high. This community service activity aims to train and empower the women farmer groups in utilizing agricultural waste into organic fertilizers that can be used to improve soil fertility and crop quality in their farming businesses. This community service activity includes several stages namely : analysis of site resources, approach methods, training, guidance, preparation and assistance of organic fertilizer production processes, production processes, monitoring of production processes and evaluation of impacts, and empowerment and participation of partners. The results of this PKM activity have provided benefits in the form of empowering and increasing the expertise of women farmer groups and the community in 8 Ilir Village, Palembang City, in utilizing and converting agricultural waste into organic fertilizer. In addition, this activity has also helped farmer groups and the community to increase their farming production by utilizing organic fertilizer produced as a source of nutrients, to improve structure and improve soil quality. Keywords: agricultural waste, community empowerment, organic fertilizer